Phylogenetic relationships of Oriental torrent frogs in the genus Amolops and its allies (Amphibia, Anura, Ranidae) - Matsui, Masafumi; Shimada, T.; Liu, W. Z.; Maryati Mohamed, Datin; Khonsue, W.; Orlov, N. (Elsevier, 2006)
We investigated the phylogenetic relationships among 20 species of Oriental torrent frogs in the genus Amolops and its allies from China and Southeast Asia based on 1346-bp sequences of the mitochondrial 12S and 16S rRNA genes. Oriental species of the tribe Ranini form a monophyletic group containing 11 clades (Rana temporaria + Pseudoamolops, R. chalconota, four clades of Amolops, Meristogenys, three clades of Huia species, and Staurois) for which the phylogenetic relationships are unresolved. The genus Amolops consists of southern Chinese, southwestern Chinese, Thai, and Vietnamese-Malaysian lineages, but their relationships are also unresolved. The separation of southern and southwestern lineages within China conforms to previous morphological and karyological results. Species of Huia do not form a monophyletic group, whereas those of Meristogenys are monophyletic. Because P. sauteri is a sister species of R. temporaria.. distinct generic status of Pseudoamolops is unwarranted.